Controlled release of simvastatin‐loaded thermo‐sensitive PLGA‐PEG‐PLGA hydrogel for bone tissue regeneration: in vitro and in vivo characteristics. Issue 11 (29th May 2015) - Yan, Qi; Xiao, Li‐Qun; Tan, Lei; Sun, Wei; Wu, Tao; Chen, Liang‐Wen; Mei, Yan; Shi, Bin
Abstract Reports on the local delivery of drug loaded injectable hydrogels for bone regeneration are currently limited. This study assessed the effect of controlled simvastatin (SIM) release from a thermo‐sensitive hydrogel in vitro and in vivo. We successfully manufactured and evaluated thermo‐sensitive poly(d, l‐lactide‐co‐glycolide)‐poly(ethylene glycol)‐poly(d, l‐lactide‐co‐glycolide) triblock copolymers (PLGA‐PEG‐PLGA) loaded with SIM. The osteogenic effect of this hydrogel was tested in vitro and in vivo. MC‐3T3 E1 cells proliferation and osteoblastic differentiation was analyzed after cultivation with the hydrogel extracts. Cells co‐cultured with SIM/PLGA‐PEG‐PLGA extracts showed an increase in mineralization and osteogenic gene expression compared to the other two groups. Additionally, the characteristics of this composite in vivo were demonstrated using a rat bone defect model. The bone defects injected with SIM/PLGA‐PEG‐PLGA hydrogel showed increased new bone formation compared to samples treated with PLGA‐PEG‐PLGA and control samples. The results of this study suggest that SIM/PLGA‐PEG‐PLGA might provide potential therapeutic value for bone healing. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 3580–3589, 2015.